Glucose- and Lipid-Related Biomarkers Are Affected in Healthy Obese or Hyperglycemic Adults Consuming a Whole-Grain Pasta Enriched in Prebiotics and Probiotics: A 12-Week Randomized Controlled Trial. Issue 10 (4th June 2019) - Angelino, Donato; Martina, Alessia; Rosi, Alice; Veronesi, Licia; Antonini, Monica; Mennella, Ilario; Vitaglione, Paola; Grioni, Sara; Brighenti, Furio; Zavaroni, Ivana; Fares, Clara; Torriani, Sandra; et al.
ABSTRACT: Background: Synbiotic foods, which combine the action of prebiotics and probiotics along the gastrointestinal tract, can affect inflammatory and glucose-related markers. Objective: The aim of this study was to investigate the effects on inflammatory and glycemia-related markers of a whole-grain pasta containing barley β-glucans and Bacillus coagulans BC30, 6086 in healthy overweight or obese volunteers. Methods: A single-blind, parallel, randomized, placebo-controlled dietary intervention study was carried out. Forty-one healthy sedentary overweight (body mass index [BMI] 25–29.9 kg/m 2 ) and obese (BMI ≥30) volunteers, aged 30–65 y and low consumers of fruit and vegetables, ate 1 serving/d of whole-grain control (CTR) or innovative (INN) pasta for 12 wk and maintained their habitual diets. Biological samples were collected at baseline and every 4 wk for primary (plasma high-sensitivity C-reactive protein [hs-CRP] and fasting plasma lipid profile) and secondary outcomes (glycemia-related markers, blood pressure, fecal microbiota composition, and body weight). Between (CTR compared with INN) and within (among weeks) group differences were tested for the whole population and for subgroups stratified by baseline values of BMI (≥30) and glycemia (≥100 mg/dL). Results: INN or CTR pasta consumption had no effect on primary and secondary outcomes over time, except for a significant increase in plasma γ-glutamyltransferase (GGT) after 12 wk of CTR pasta consumption. Comparisons between intervention groups revealed differences only at 12 wk: plasma GGT was higher in the CTR group; plasma hs-CRP, plasma LDL/HDL cholesterol ratio, and Bifidobacterium spp. were lower in the INN subgroup of obese volunteers; plasma resistin was lower and Faecalibacterium prausnitzii abundance was higher in the INN subgroup of hyperglycemic volunteers. Conclusions: A daily serving of a synbiotic whole-grain pasta had limited effects on primary and secondary outcomes in the entire group of volunteers but affected glycemia- and lipid-related markers and resistin in a subgroup of healthy obese or hyperglycemic volunteers. This trial was registered at clinicaltrials.gov as NCT02236533.